Galangin Suppresses Pro-Inflammatory Gene Expression in Polyinosinic-Polycytidylic Acid-Stimulated Microglial Cells - Choi, Min-Ji; Park, Jin-Sun; Park, Jung-Eun; Kim, Han Su; Kim, Hee-Sun (Biomolecules & therapeutics, 2017)
Galangin (3,5,7-trihydroxyflavone) is a polyphenolic compound abundant in honey and medicinal herbs, such as . In this study, we investigated the anti-inflammatory effects of galangin under and neuroinflammatory conditions caused by polyinosinic-polycytidylic acid (poly(I:C)), a viral mimic dsRNA analog. Galangin suppressed the production of nitric oxide, reactive oxygen species, and pro-inflammatory cytokines in poly(I:C)-stimulated BV2 microglia. On the other hand, galangin enhanced anti-inflammatory interleukin (IL)-10 production. Galangin also suppressed the expression of pro-inflammatory markers in poly(I:C)-injected mouse brains. Further mechanistic studies showed that galangin inhibited poly(I:C)-induced nuclear factor (NF)-κB activity and phosphorylation of Akt without affecting MAP kinases. Interestingly, galangin increased the expression and transcriptional activity of peroxisome proliferator-activated receptor (PPAR)-γ, known to play an anti-inflammatory role. To investigate whether PPAR-γ is involved in the anti-inflammatory function of galangin, BV2 cells were pre-treated with PPAR-γ antagonist before treatment of galangin. We found that PPAR-γ antagonist significantly blocked galangin-mediated upregulation of IL-10 and attenuated the inhibition of tumor necrosis factor (TNF)-α and IL-6 in poly(I:C)-stimulated microglia. In conclusion, our data suggest that PI3K/Akt, NF-κB, and PPAR-γ play a pivotal role in mediating the anti-inflammatory effects of galangin in poly(I:C)-stimulated microglia.